(untitled) (Baghdad Science Journal, 2016)
In the present work, the critical micelle concentration (CMC) of the solution of Sodium dodecyl sulfate (SDS) as anionic surfactant, Cocamidopropyl Betaine (CAPB) as amphoteric surfactant, and their mixture have been determined using surface tension and conductivity measurements at a temperature range 293 -323 K. The adsorption and thermodynamic micellization parameters (?G?m, ?G?ads, ?max ,Amin,?cmc ) for individual surfactants was calculated. Rosen model which is focuses on the adsorbed mixed surfactant film at the air/solution interface was used to calculate the interaction parameter ( ?? ) at the interface and the activity coefficients g1 and g2. The results indicate that the CMC of the individual surfactants was affected by the temperature at the temperature range studied. Also, the results indicate a synergistic effect present at the air – solution mixed film of surfactants.